2012
DOI: 10.7847/jfp.2012.25.3.159
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the immunogenicity between bacterial ghost and formalin-killed bacteria for Vibrio vulnificus

Abstract: Vibrio vulnificus ghosts (VVG) were generated using a mobilizable vector including a thermosensitive expression cassette by conjugation. The vaccine potential of VVG was investigated in mouse. Mice immunized with VVG showed significantly higher antibody titer than those with formalin-killed V. vulnificus. The present study supports the conceptive usefulness of bacterial ghosts as vaccine candidates.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2016
2016
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 24 publications
0
3
0
Order By: Relevance
“…More than 80 serotypes of V. parahaemolyticus have been described worldwide, based on the O and K antigenic properties [22]. To date, some BGs have been produced from other Vibrio species ( V. cholera , V. anguillarum , V. vulnificus ) by using the lysis E -gene system [4,5,23,24], but no BGs have been reported from V. parahaemolyticus . In the present study, we determined the MIC of various chemicals (six acids and one alkali) on V. parahaemolyticus cells and characterized their efficiencies to produce V. parahaemolyticus ghosts (VPGs).…”
Section: Introductionmentioning
confidence: 99%
“…More than 80 serotypes of V. parahaemolyticus have been described worldwide, based on the O and K antigenic properties [22]. To date, some BGs have been produced from other Vibrio species ( V. cholera , V. anguillarum , V. vulnificus ) by using the lysis E -gene system [4,5,23,24], but no BGs have been reported from V. parahaemolyticus . In the present study, we determined the MIC of various chemicals (six acids and one alkali) on V. parahaemolyticus cells and characterized their efficiencies to produce V. parahaemolyticus ghosts (VPGs).…”
Section: Introductionmentioning
confidence: 99%
“…Vaccination concurrently triggered both innate immune response and adaptive immunity, which is very important for the control of bacterial diseases. Traditional inactivation of bacteria by formalin may destroy bacterial antigenic epitopes (Kwon, 2012). The study found that bacterial ghost can effectively stimulate innate and adaptive immune responses (Felnerova et al, 2004).…”
Section: Discussionmentioning
confidence: 99%
“…The Gram-negative bacteria, under the impact of Lysis E, result in the expulsion of cytoplasmic contents and the formation of the bacterial shell structure, namely bacterial ghost vaccine. In recent years, a number of ghost vaccines have been studied, such as Escherichia coli (Mayr et al, 2005), E. tarda (Lee et al, 2008), V. anguillarum (Kwon et al, 2009), Aeromonas hydrophila (Chu et al, 2008) Flavobacterium cloumnare (Zhu et al, 2012) and V. vulnificus (Kwon, 2012). With bacterial ghosts, surface protein antigens remain intact, and these induce the body's humoral and cellular immune response (Felnerova et al, 2004).…”
Section: Introductionmentioning
confidence: 99%